(untitled) (Perner’s Contacts, 2010)
This paper deals with reasons of Authorized Economic Operator certification uprising like a new effect in custom affairs of European Union. Obtaining of AEO certificate is followed with a lot of demands and detection what is often very blind and incomprehensible for asking economic subject. This is possible to be a reason of quietly little amount of subjects that have this certificate obtained in Czech and Slovak Republic. The obtaining of this certificate is undisputed demonstration of quality and reliability of economic subject.